Noise and low‐frequency sound levels due to aerial fireworks and prediction of the occupational exposure of pyrotechnicians to noise. Issue 6 (29th November 2016) - Tanaka, Tagayasu; Inaba, Ryoichi; Aoyama, Atsuhito
Abstract : Objectives: This study investigated the actual situation of noise and low‐frequency sounds in firework events and their impact on pyrotechnicians. Methods: Data on firework noise and low‐frequency sounds were obtained at a point located approximately 100 m away from the launch site of a firework display held in "A" City in 2013. We obtained the data by continuously measuring and analyzing the equivalent continuous sound level ( L eq) and the one‐third octave band of the noise and low‐frequency sounds emanating from the major firework detonations, and predicted sound levels at the original launch site. Results: Sound levels of 100‐115 dB and low‐frequency sounds of 100‐125 dB were observed at night. The maximum and mean L eq values were 97 and 95 dB, respectively. The launching noise level predicted from the sounds (85 dB) at the noise measurement point was 133 dB. Occupational exposure to noise for pyrotechnicians at the remote operation point (located 20‐30 m away from the launch site) was estimated to be below 100 dB. Conclusions: Pyrotechnicians are exposed to very loud noise (>100 dB) at the launch point. We believe that it is necessary to implement measures such as fixing earplugs or earmuffs, posting a warning at the workplace, and executing a remote launching operation to prevent hearing loss caused by occupational exposure of pyrotechnicians to noise. It is predicted that both sound levels and low‐frequency sounds would be reduced by approximately 35 dB at the remote operation site.